(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The inquiry model discussed in the article gives a clear picture of the roles of both the educator as well as the learners in the context of inquiry based learning classrooms. The paper also discusses on the inquiry based classroom activities that emphasize on the application of the latest educational technology such as the Internet.